Parents' perception of allergic or food-intolerant children in relation to disease - Moimaz, Suzely Adas Saliba [UNESP]; Amaral, Marcelo Augusto [UNESP]; Miotto, Aline Maria Malachini; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Tânia Adas [UNESP] (Faculdade de Filosofia e Ciências, 2019)
Introduction: Cow' milk protein allergy (CMPA) and lactose intolerance (LI) negatively affect the quality of life of patients and their families. Objective: To analyse the perception parents of children with CMPA or LI regarding aspects of health, emphasizing their oral health and the factors involved in the treatment of allergy/food intolerance. Methods: Qualitative research employing focus groups, with a sample of 12 parents of children with CMPA or LI (two groups), including the participation of a researcher/moderator, an observer, and six participants in each group and a plan with guiding questions. Discourses were recorded and transcribed, and textual contents were processed in software IRAMUTEQ and analysed by the descendant hierarchical classification (DHC) technique, content analysis, and word cloud. Results: Six categories were derived from DHC-multivariate analysis: (1) children formula, (2) oral health, (3) nutritional aspects, (4) treatment, (5) disease' stigma, and (6) health services. The thematic axes were derived from nutritional, assistance, and care categories. Reports of different oral diseases were given by parents regarding food allergy or intolerance in their children, such as frequent caries, teeth spots, pain, and sensitive teeth. Conclusion: Parents' perception of CMPA/LI in their children is affected by nutritional factors and the stigma caused by the disease, with special reference to the importance given to children' oral health and reports about difficulties in the access to health services with multi-professional teams.
Keywords: Lactose intolerance; Milk hypersensitivity; Qualitative analysis